STRUCTURAL, CHEMICAL, AND ISOTOPIC MICROANALYTICAL INVESTIGATIONS OF GRAPHITE FROM SUPERNOVAE - Croat T.K.; Bernatowicz T.; Amari S.; Messenger S.; Stadermann F.J. (My University, 2003)
We report the results of coordinated ion microprobe and transmission electron microscope (TEM) studies of presolar graphites from the KE3 separate (1.65-1.72 g/cm3) of the Murchison CM2 meteorite. Isotopic analysis of individual graphites (1-12 μm) with the ion microprobe shows many to have large 18O excesses combined with large silicon isotopic anomalies, indicative of a supernova (SN) origin. Transmission electron microscopy (TEM) of ultramicrotome slices of these SN graphites revealed a high abundance (25-2400 ppm) of internal titanium carbides (TiCs), with a single graphite in some cases containing hundreds of TiCs. Isotopic compositions of individual TiCs by nanoscale resolution secondary ion mass spectrometry (NanoSIMS) confirmed their presolar origin. In addition to TiCs, composite TiC/Fe grains (TiCs with attached iron-nickel subgrains) and solitary kamacite internal grains were found. In the composite grains, the attached iron phase (kamacite [0-24 at. % Ni] or taenite [up to 60 at. % Ni]) was epitaxially grown onto one or more TiC faces. In contrast to the denser Murchison KFC1 graphites, no Zr-Ti-Mo carbides were observed. The average TiC diameters were quite variable among the SN graphites, from 30 to 232 nm, and were generally independent of the host graphite size. TiC grain morphologies ranged from euhedral to anhedral, with the grain surfaces exhibiting variable degrees of corrosion, and sometimes partially amorphous rims (3 to 15 nm thick). Partially amorphous rims of similar thickness were also observed on some solitary kamacite grains. We speculate that the rims on the internal grains are most plausibly the result of atom bombardment caused by drift of grains with respect to the ambient gas, requiring relative outflow speeds ~100 km/s (i.e., a few percent of the SN mass outflow speed).Energy dispersive X-ray spectrometry (EDXS) of TiCs revealed significant V in solid solution, with an average V/Ti ratio over all TiCs of ~83% of the solar value of 0.122. Significant variations about the mean V/Ti ratio were also seen among TiCs in the same graphite, likely indicating chemical equilibration with the surrounding gas over a range of temperatures. In general, the diversity in internal TiC properties suggests that TiCs formed first and had substantially diverse histories before incorporation into the graphite, implying some degree of turbulent mixing in the SN outflows.In most graphites, there is a decrease in the number density of TiCs as a function of increasing radial dis- tance, caused by either preferential depletion of TiCs from the gas or an acceleration of graphite growth with decreasing ambient temperature. In several graphites, TiCs showed a trend of larger V/Ti ratios with increasing distance from the graphite center, an indication of progressive equilibration with the surrounding gas before they were sequestered in the graphites. In all but one graphite, no trend was seen in the TiC size vs. distance from the graphite center, implying that appreciable TiC growth had effectively stopped before the graphites formed, or else that graphite growth was rapid compared to TiC growth. Taken together, the chemical variations among internal grains as well as the presence of partially amorphous rims and epitaxial Fe phases on some TiCs clearly indicate that the phase condensation sequence was TiC, followed by the iron phases (only found in some graphites) and finally graphite. Since graphite typically condenses at a higher temperature than iron at low pressures (<10-3 bars) in a gas with C > O and otherwise solar composition, the observed condensation sequence implies a relative iron enrichment in the gas or greater supersaturation of graphite relative to iron.The TEM observations allow inferences to be made about the physical conditions in the gas from which the grains condensed. Given the TiC sizes and abundances, the gas was evidently quite dusty. From the observed TiC size range of ~20 nm to ~500 nm (assuming ~1 yr growth time and T ~ 1800°K), we infer minimum Ti number densities in the gas to be ~7 x 104 to ~2 x 106 atoms/cc, respectively. Although the gas composition is clearly not solar, for scale, these number densities would correspond to a pressure range of ~0.2 μbar to ~5.0 μbar in a gas of solar composition. They also correspond to minimum TiC grain number densities of ~3 x 10-4 to ~0.2 grains/cc, assuming complete condensation of Ti in TiC. We estimate the maximum ratio of mean TiC grain separation distance in the gas to grain diameter from the Ti number densities as ~3 x 105 to ~1 x 106.